Sistem Pendukung Keputusan Pemilihan Lahan Penanaman Sirih Menggunakan Metode Analytical Hirarchy Process (AHP) - Rezki; Umar, Rusydi; Fadlil, Abdul (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
Land is a prerequisite that must be considered in betel leaf cultivation, as it significantly influences the quality of the grown betel leaves. Poor-quality land can result in decreased betel leaf harvest, reduced shelf life, susceptibility to rot, curling, and lower selling prices. Based on this issue, a system is needed to facilitate the community in selecting the appropriate land for betel leaf cultivation, which is the Decision Support System (DSS). In this research, the SPK utilizes the Analytic Hierarchy Process (AHP) method with criteria such as soil pH, air temperature, rainfall, soil elevation, and sunlight, as well as alternatives represented by the villages of Mariat Gunung, Klaru, Klamono, and Malasom. The ranking is determined based on a consistency ratio value of <0.1, which is interpreted as being appropriate according to the CR calculation theory. The highest-ranking land is found in Klaru Village (rank 1), followed by Mariat Gunung (rank 2), Klamono (rank 3), and Malasom (rank 4). In conclusion, the AHP method can be utilized for the decision-making process in selecting land for betel leaf cultivation